TECHNOLOGIES FOR USING SOFT SKILLS IN DEVELOPING TOLERANT THINKING IN FUTURE TEACHERS (Eureka Journal of Education & Learning Technologies, 2026)
This article is devoted to the problem of development of professional knowledge and shills of tesachers music.
Keywords: Music art, creative means, art, enlightenment, song, melody, method, facilities